GENETIC VARIABILITY AND ASSOCIATION AMONG SEEDLING TRAITS OF ZEA MAYS UNDER DROUGHT STRESS CONDITIONS - Haseeb, A; Nawaz, A; Rao, MQA; Ali, Q; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
Maize is an important food crop for human and feed for animals or livestock. It is highly sensitive for abiotic and biotic stress conditions. An experiment was conducted in the greenhouse of Institute of Molecular Biology and Biotechnology, The University of Lahore for the determination of effects of drought on maize growth related seedling traits. Four maize genotypes/varieties viz., B-316, Raka-poshi, Pak-Afghoi and EV-1097Q were grown to evaluate the effects of drought stress. Four drought treatments were used including 20% irrigation water, 40% irrigation water, 60% irrigation water, 80% irrigation water, 90% irrigation water and control or 100% irrigation water. It was found that the genotypes B-316 and Raka-poshi showed better performance for all studied traits especial shoot and root length as compared with other two genotypes EV-109Q and Pak-Afghoi. The minimum effects of drought were reported at control and 90% irrigation water. The effects of drought were increased with the increase in concentration of drought stress. The adverse drought effects were reported under the treatment of drought at 20% and 40% irrigation water. The higher genetic advance and heritability was recorded for root length, shoot length, dry shoot weight and dry root weight. The significant correlation was recorded between root length, shoot length and dry shoot weight. The higher contribution for shoot length was reported for root length, dry shoot weight and number of roots per plant. It was concluded from study that the selection of maize genotypes on the basis of root length, shoot length and dry shoot weight may be fruitful to produce drought stress tolerance maize hybrids and synthetic varieties.